Protective Effect of Lycopene on Oxidative Stress and Antioxidant Status in Cyprinus carpio during Cypermethrin Exposure - Yonar, M. Enis (Wiley, 2013)
The aim of this study was to investigate the ameliorative properties of lycopene against the toxic effects of cypermethrin (CYP) by examining oxidative damage markers such as lipid peroxidation and the antioxidant defense system components in carp (Cyprinus carpio). The fish were divided into seven groups of 10 fish each and received the following treatments: group 1, no treatment; group 2, orally administered corn oil; group 3, oral lycopene (10 mg/kg body weight); group 4, exposure to 0.202 g/L CYP; group 5, exposure to 0.202 g/L CYP plus oral administration of 10 mg/kg lycopene; group 6, exposure to 0.404 g/L CYP; and group 7, exposure to 0.404 g/L CYP plus oral administration of 10 mg/kg lycopene. Treatment was continued for 28 days, and at the end of this period, blood and tissue (liver, kidney, and gill) samples were collected. Levels of malondialdehyde (MDA) and reduced glutathione (GSH) as well as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activities were determined in blood and tissues for measurement of oxidant-antioxidant status. MDA level, as an index of lipid peroxidation, increased in blood and tissues. Antioxidant enzyme activities in blood and tissues were modified in CYP groups compared with controls. Administration of lycopene ameliorated these parameters. The present results suggest that administration of lycopene might alleviate CYP-induced oxidative stress. (c) 2011 Wiley Periodicals, Inc. Environ Toxicol 28:609-616, 2013.
Keywords: pesticides; pyrethroid insecticide; cypermethrin; lycopene; oxidative stress; antioxidant enzymes; fish